A pilot investigation of anterior tilt use among power wheelchair users. (17th February 2021) - Rice, Laura A.; Yarnot, Rebecca; Mills, Sarah; Sonsoff, Jacob
Abstract: Purpose: To examine the influence of use of the anterior tilt-in-space power seat function on performance of functional activities, physical health, and user satisfaction on among power wheelchair users. Materials and methods: Ten full-time power wheelchair users with a seat elevator on their current chair participated in a mixed-methods, repeated measures study. At Visit 1 participants completed the Wheelchair Outcome Measure, Functional Mobility Assessment, Wheelchair Users Shoulder Pain Index, Fatigue Severity Scale, and the Spinal Cord Injury Secondary Conditions Scale. Physical assessments were performed to examine transfer quality (transfer assessment instrument), functional reach, activities of daily living (performance assessment of self-care skills), seated balance (function in sitting test), spasticity, respiratory function, and speech production. Approximately 3 days later (Visit 2), participants were trained on use and provided a power wheelchair with anterior tilt to trial for two weeks. After two weeks (Visit 3), the Visit 1 protocol was repeated and a semistructured interview conducted. Results: Participants lived with disabilities of cerebral palsy, spinal muscular atrophy and multiple sclerosis. With use of anterior tilt, significant improvements were seen among safety of meal preparation, p = 0.033, dz = 0.91 and functional reach in the vertical direction, p = 0.000, dz = 2.62. Subjectively, participants found anterior tilt helpful in performance of reaching tasks in but found the safety equipment restrictive. Conclusion: Preliminary results indicate that use of the anterior tilt may help to improve performance of functional activities. Additional research is needed to examine the long-term influence of the technology. Implications for rehabilitation: The anterior tilt seat function changes the seat angle orientation in relation to the ground in the sagittal plane and angles the seat forward. As a result, the individual using the assistive technology is positioned in a semistanding position. Preliminary results of this study indicate that with use of anterior tilt, safety of meal preparation and functional reach in the vertical direction significantly improved. Subjectively, participants found anterior tilt helpful in performance of reaching tasks but found the safety equipment restrictive. Additional research is needed to examine the long-term influence of anterior tilt on functional activities, physical health and user satisfaction on among a large and diverse group of power wheelchair users.